How the relationship between individual and social factors informs the narrowing of gender gaps in elementary mathematical achievements - Paz-Baruch, Nurit; Spektor-Levy, Ornit (Frontiers in Education, 2024)
Few scholarly studies have examined gender gaps vis-à-vis various types of mathematical problems by controlling for individual factors (e.g., general intelligence and self-regulated learning [SRL]) and social factors (e.g., the school’s socioeconomic status [SES]) among elementary school students, as addressed in this study. Achievements on three types of mathematical tasks (operations with numbers, geometry, and word problems) and general intelligence scores were obtained from elementary school students. Information regarding students’ SRL was obtained from a rating scale designed for the teachers. Results showed that boys’ achievements were significantly higher in word problem-solving and geometry tests but not in operation with numbers tests. The results concerning word problems suggest that the effect of the school’s SES level on the gender gap decreased in accordance with the increase in the school’s SES level. The significant interaction between gender and SRL indicated that the effect of students’ SRL level on the gender difference in the students’ performance on the geometry test increased in accordance with the increase in the SRL level. General intelligence contributed to individual differences in word problems and geometry, but not on operations with numbers. The analyses showed that SRL contributed to mathematical performance in all tasks. Directions for future research and implications for narrowing these gender gaps are discussed.